Morphological Analysis by Surface Patterns and by Graph - Said, Iazzi; Abdellah, Yousfi; Mostafa, Bellafkih; Driss, Aboutajdine (International Journal of Engineering and Technology, 2018)
Â In this article, we propose a comparison between our two morphological analyzers, which we have developed in recent years. The first is based on surface patterns Arabic words, the second is an analyzer which combines Buckwalter approach and the approach of morphological analysis in base graph. The comparison is made on a corpus of 1400 Arabic words that generalize all cases of Arabic derived words. The results obtained show the interest and the advantages of each analyzer.Â Â